Separatism as a Threat to the National Security of the Republic of Kazakhstan: Problems of Counteraction - KILYBAYEV, Nurlybek A.; ESTEUSIZOV, Yernar N. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
The authors of the research consider issues of counteracting modern manifestations of separatism in the context of ensuring regional security in accordance with the international and criminal legislation of the Republic of Kazakhstan. The analysis results are exemplified not only by separatist manifestations in certain states but also their possible spread through Central Asia due to common interests and cross-border cooperation. The authors study the criminal law of the Republic of Kazakhstan regulating liability for separatist activities and draw conclusions on improving the existing legislation to effectively prevent and combat separatist crimes. They also consider aspects of international cooperation aimed at fighting against separatism in the context of their historical formation and prevention prospects.